Integrating substance abuse care with community diabetes care: implications for research and clinical practice - Ghitza UE; Wu LT; Tai B (Dove Medical Press, 2013)
Udi E Ghitza,1 Li-Tzy Wu,2 Betty Tai11Center for the Clinical Trials Network, National Institute on Drug Abuse, National Institutes of Health, United States Department of Health and Human Services, Bethesda, MD, 2Department of Psychiatry and Behavioral Sciences, Duke University Medical Center, Durham, NC, USAAbstract: Cigarette smoking and alcohol use are prevalent among individuals with diabetes in the US, but little is known about screening and treatment for substance use disorders in the diabetic population. This commentary discusses the scope and clinical implications of the public health problem of coexisting substance use and diabetes, including suggestions for future research. Diabetes is the seventh leading cause of death in the US, and is associated with many severe health complications like cardiovascular disease, stroke, kidney damage, and limb amputations. There are an estimated 24 million adults in the US with type 2 diabetes. Approximately 20% of adults aged 18 years or older with diabetes report current cigarette smoking. The prevalence of current alcohol use in the diabetic population is estimated to be around 50%–60% in epidemiological surveys and treatment-seeking populations. Cigarette smoking is associated with an increased risk of type 2 diabetes in a dose-dependent manner and is an independent modifiable risk factor for development of type 2 diabetes. Diabetic patients with an alcohol or other drug use disorder show a higher rate of adverse health outcomes. For example, these patients experience more frequent and severe health complications as well as an increased risk of hospitalization, and require longer hospital stays. They are also less likely to seek routine care for diabetes or adhere to diabetes treatment than those without an alcohol or other drug use disorder. The Affordable Care Act of 2010 and the Mental Health Parity Act and Addiction Equity Act of 2008 provide opportunities for facilitating integration of preventive services and evidence-based treatments for substance use disorders with diabetes care in community-based medical settings. These laws also offer emerging areas for research.Keywords: addiction, illicit drug use, substance use disorder, substance abuse treatment, alcohol use, diabetes care, primary care, screening, brief intervention